2016
DOI: 10.1186/s12884-016-0850-y
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight centiles by gestational age for twins born in south India

Abstract: BackgroundBirth weight centile curves are commonly used as a screening tool and to assess the position of a newborn on a given reference distribution. Birth weight of twins are known to be less than those of comparable singletons and twin-specific birth weight centile curves are recommended for use. In this study, we aim to construct gestational age specific birth weight centile curves for twins born in south India.MethodsThe study was conducted at the Christian Medical College, Vellore, south India. The birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
2
12
0
1
Order By: Relevance
“…It has been used by the Multicentre Growth Reference Study (MGRS) of World Health Organization (WHO) group in constructing growth reference curves for school-age children and adolescents. 2 GAMLSS is also widely used to develop various growth references for such characteristics as lung function, 3 birth weight, 4 grip strength, 5 and blood pressure. 6 However, it has not been used to develop growth curves for assessing male external genitalia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used by the Multicentre Growth Reference Study (MGRS) of World Health Organization (WHO) group in constructing growth reference curves for school-age children and adolescents. 2 GAMLSS is also widely used to develop various growth references for such characteristics as lung function, 3 birth weight, 4 grip strength, 5 and blood pressure. 6 However, it has not been used to develop growth curves for assessing male external genitalia.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, although there are the continuous efforts, trying to establish fetal growth curve for twins, but the issue has not been resolved. The existing data has inherent limitations, for example, some of the data came from birth weight and cannot be applied to the growth and development assessment during pregnancy 24,[35][36][37][38] , some others recruited subjects by small sample size 5,11,15 or without exclusion of high-risk pregnancy 5,12,16 . In the present study, we got over the limitations and largely promised our growth reference chart customized for chorionicity and mode of conception a more reliable tool to distinguish cases with fetal growth restriction in twins 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we also compared our estimated 50 th birthweight percentile values to other twin birthweight studies that compiled reference ranges split by chorionicity 15,18 . When compared to the Ananth et al 18 study, the largest difference between birthweight in DCDA twins occurred at 35 weeks' gestation.…”
Section: Interpretation Of Study Findings and Comparison With Existing Literaturementioning
confidence: 99%
“…The differences discussed above, could be as a result of population variance. However, it should be noted that both the data presented by these studies 15,18 are based on observed birthweight measurements.…”
Section: Interpretation Of Study Findings and Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation